064 Identifying, Describing and Evaluating Guideline Implementability Tools. (15th August 2013) - Cheng, J; Gagliardi, A; Brouwers, M; Bhattacharyya, O
Abstract : Background: Research shows that guidelines are more easily translated to practice when accompanied by information that helps users accommodate, implement and evaluate use of the recommendations. Guidelines vary in whether and how they offer such information, which we refer to as guideline implementability tools (GItools). Objectives: To identify, describe and evaluate exemplar GItools that address Resource Implications, Implementation and Evaluation, and suggest how they could be improved. Methods: GItools were identified in several sources (guidelines, Medline, professional organisation web sites, Implementation Science, Internet, expert referrals) and two individuals independently assessed each on criteria recommended by G-I-N members: purpose statement, instructions for use, citations for source of content, and how it was developed. Results: The search produced 228 potential tools. Of these 94 were ineligible and 63 met no assessment criteria. Of the remaining 71 tools, 13 (18.3%), 24 (33.8%), 23 (32.4%) and 11 (15.5%) met 1, 2, 3 and 4 criteria, respectively; and 57 (80.3%), 37 (52.1%), 41 (57.7%) and 41 (57.7%) provided purpose, instructions, citations and development details, respectively. Most tools addressed Implementation (44, 62.0%). Twenty-eight (39.4%) were guideline-specific and 43 (60.6%) were generic. Discussion: Few GItools met all assessment criteria. GItools could be more informative across all criteria. Few GItools were available to help users assess resource needs or evaluate guideline use. Many GItools were applicable to a variety of guidelines. Implications: We identified a number of ways to improve GItools. Collaborative development and sharing of both generic and condition-specific GItools could make efficient use of resources.